AN INVESTIGATION OF THE RELATIONSHIP BETWEEN FITNESS LEVELS, SELF-EFFICACY, AND LOCUS OF CONTROL ON ACADEMIC ACHIEVEMENT OF MIDDLE SCHOOL STUDENTS - Attoh, P. A.; Philmon, V. M. (European Scientific Journal, ESJ, 2015)
This study investigated the effect fitness level, self-efficacy and locus of control have on the academic achievement of eighth grade students (n=115) studying in a Mid-Atlantic region middle school (2011-2012 school year). It was hypothesized that the students who had high fitness scores, high level of self-efficacy and high internal locus of control would also have high academic achievement scores in math and reading. The quantitative research design involved the single-stage sampling method. Data were analyzed using multiple regression analysis. The study has revealed significant relationship between academic achievement, locus of control and self-efficacy.